Managing children’s character development in the digital era: A systematic literature review of parenting, digital literacy, and peer influence from an educational management perspective - Deny Haryadi; Wahyu Widada; Nurul Astuti Yensy (CV. FOUNDAE, 2026)
Background: Rapid digital development has transformed the way children learn, communicate, and build character. Moral and social development is now shaped not only by family and school environments but also by online interaction and peer networks. Despite growing attention to this issue, studies commonly discuss parenting, digital literacy, and peer influence independently rather than as interconnected factors within education. Aims: This review investigates the relationship between parenting practices, digital literacy, and peer influence in supporting children’s character development in the digital era. Methods: A Systematic Literature Review (SLR) was conducted using the PRISMA 2020 procedure. Relevant studies were obtained from the Scopus database through predetermined selection criteria. After the screening process, 15 eligible studies published between 2016 and 2026 were analysed using thematic synthesis. Results: The review found that supportive parenting plays an important role in shaping children’s values, self-control, and social behaviour. Digital literacy helps children apply these values appropriately in online environments, while peer interaction influences how values are strengthened or challenged in daily life. Schools also contribute by connecting family guidance, digital learning, and peer interaction through educational policies and learning practices. Conclusion: Children’s character development in the digital era develops through interaction between family, school, and social environments. Integrated cooperation among these domains is necessary to support effective and sustainable character education.